Risk factors for mortality in Down syndrome. (8th April 2015) - Uppal, H.; Chandran, S.; Potluri, R.
Abstract Background Down syndrome is a genetic condition that contributes to a significantly shorter life expectancy compared with the general population. We investigated the most common comorbidities in a population of acute hospital patients with Down syndrome and further explored what the most common risk factors for mortality are within this population. Method From our database of one million patients admitted to National Health Service (NHS) Trusts in northern England, we identified 558 people who had Down syndrome. We compared this group with an age‐ and gender‐matched control group of 5580 people. Results The most prevalent comorbid diseases within the Down's population were hypothyroidism (22.9%) and epilepsy (20.3%). However, the conditions that had the highest relative risks (RRs) in the Down's population were septal defects and dementia. Respiratory failure, dementia and pneumonia were the most significantly related comorbidities to mortality in the Down syndrome population. In the control population, respiratory failure, dementia and renal failure were the most significant disease contributors. When these contributors were analysed using multivariate analysis, heart failure, respiratory failure, pneumonia and epilepsy were the identified risk factors for in‐hospital mortality in the Down syndrome population. Respiratory failure was the sole risk factor for mortality in the Down syndrome population [RR = 9.791 (1.6–59.9) P ≤ 0.05], when compared with the risk factors for mortality in the control population. Conclusions There is significant medical morbidity in Down syndrome. This morbidity contributes to the lower life expectancy. Respiratory failure is a risk factor for mortality in Down syndrome. We need to thoroughly investigate people with Down syndrome to ensure any treatable illnesses are well managed.